2019
DOI: 10.1002/aoc.5283
|View full text |Cite
|
Sign up to set email alerts
|

Organotin(IV) complexes of NSAID, ibuprofen, X‐ray structure of Ph3Sn(IBF), binding and cleavage interaction with DNA and in vitro cytotoxic studies of several organotin complexes of drugs

Abstract: This study encompasses the synthesis and characterization of organotin(IV) derivatives of non‐steroidal anti‐inflammatory drug ibuprofen (IBF), viz. [(Me3Sn)(IBF)] (1), [(Bu3Sn)(IBF)] (2), [Ph3Sn(IBF)] (3), {[Me2Sn(IBF)]2O}2 (4) and [Bu2Sn(IBF)2] (5). The crystal structure of complex 3, [Ph3Sn(IBF)], indicates a highly distorted tetrahedral (td) geometry with anisobidentate mode of coordination of the carboxylate group with tin atom, and a similar structure has been proposed for other two triorganotin(IV) deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Furthermore, the presence of peaks was demonstrated between 443 and 482 cm −1 , and 543 and 555 cm −1 , which are related to stretching Sn-O bond frequency, and stretching Sn-C bond frequency, respectively. This is obvious evidence regarding the complex formation [35].…”
Section: Characterization Of Synthesized Complexesmentioning
confidence: 75%
See 1 more Smart Citation
“…Furthermore, the presence of peaks was demonstrated between 443 and 482 cm −1 , and 543 and 555 cm −1 , which are related to stretching Sn-O bond frequency, and stretching Sn-C bond frequency, respectively. This is obvious evidence regarding the complex formation [35].…”
Section: Characterization Of Synthesized Complexesmentioning
confidence: 75%
“…Furthermore, the presence of peaks was demonstrated between 443 and 482 cm −1 , and 543 and 555 cm −1 , which are related to stretching Sn-O bond frequency, and stretching Sn-C bond frequency, respectively. This is obvious evidence regarding the complex formation [35]. The FTIR spectrum for Ibuprofen was compared with the spectra of organotin(IV) complexes to clarify the bonding sites of ligand molecules when coordinated with organotin(IV) compounds.…”
Section: Characterization Of Synthesized Complexesmentioning
confidence: 99%
“…However, the variations in the in vitro cytotoxicity among 1 and 2 across tumor cell lines could also be related to a different kinetic and mechanistic behavior. Recently, the cytotoxicity for nBu 3 Sn(ibuprofen) and Ph 3 Sn(ibuprofen) were reported; however, in practice, the results should not be compared directly, since these were investigated using DU145 (prostate cancer), HCT-15 (colon adenocarcinoma), Caco-2 (colorectal adenocarcinoma) human cancer cell lines [55]. The observed results convincingly support the view that compounds 1 and 2 are potent cytotoxic agents and deserve further investigation as potential anticancer agents.…”
Section: 4cytotoxicity Studiesmentioning
confidence: 99%
“…Numerous studies have demonstrated that metal-NSAID complexes, including zinc­(II)-NSAIDs, iridium­(III)-aspirin, ruthenium­(II)-NSAIDs, nickel­(II)-NSAIDs, silver­(I)-NSAIDs, manganese­(II)-NSAIDs, , and organotin­(IV)-NSAIDs, also exhibit potent cytotoxic activity against several cancer cells. The most likely modes of action of these complexes are increase of COX-2 selectivity, , induction of ROS, interaction with serum albumins, and intercalation of DNA .…”
Section: Development Of Nsaid Analogs and Their Applications In Cance...mentioning
confidence: 99%